The development of Schoology web-based learning media with GeoGebra to improve the ICT literacy on quadratic functions - Fatahillah, Arif; Puspitasari, Irsalina Dwi; Hussen, Saddam (JRAMathEdu (Journal of Research and Advances in Mathematics Education), 2020)
The use of technology in learning is essential for developing students' ICT literacy. However, the application of technology as a learning media remains limited. The purpose of this study is to develop a learning media to enhance students' ICT literacy. This research is conducted using a 4-D model, which consists of four stages: defining, designing, developing, and disseminating. This learning media is developed based on ICT literacy indicators. The study participants are 33 of 10th-grade students at one of the public vocational schools in Jember, East Java. Data collection methods consist of validation sheets, tests, questionnaires, interviews, and observations.Â  The expert validation is used to validate the media, while the students' response questionnaire determines the practicality. The validity result shows that the media can be used to measure ICT literacy. Moreover, the practicality of media also shows that it can be easily applied. Furthermore, the effectiveness of learning media is obtained from the N-Gain average of test and ICT literacy questionnaire. The observation data also support the effectiveness of the media during the implementation. The result shows that the media confirmed to be effective as it can improve the students' ICT literacy. To sum up, the Schoology web-based learning media with GeoGebra is useful to improve ICT literacy on quadratic functions